2021
DOI: 10.3390/cells10020398
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of the Natriuretic Peptide/cGMP System to Hyperammonaemia in Rat C6 Glioma Cells and GPNT Brain Endothelial Cells

Abstract: C-type natriuretic peptide (CNP) is the major natriuretic peptide of the central nervous system and acts via its selective guanylyl cyclase-B (GC-B) receptor to regulate cGMP production in neurons, astrocytes and endothelial cells. CNP is implicated in the regulation of neurogenesis, axonal bifurcation, as well as learning and memory. Several neurological disorders result in toxic concentrations of ammonia (hyperammonaemia), which can adversely affect astrocyte function. However, the relationship between CNP a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 92 publications
1
6
0
Order By: Relevance
“…GC-B has a critical role in the bifurcation of axons during development ( Schmidt et al, 2018 ) extending previous observations that the natriuretic peptide systems play roles in regulating neural development ( DiCicco-Bloom et al, 2004 ; Müller et al, 2009 ). Collectively, these findings support the notion that CNP is a prominent regulatory factor in the nervous system ( Kuhn, 2016 ; Regan et al, 2021 ).…”
Section: Discussionsupporting
confidence: 83%
“…GC-B has a critical role in the bifurcation of axons during development ( Schmidt et al, 2018 ) extending previous observations that the natriuretic peptide systems play roles in regulating neural development ( DiCicco-Bloom et al, 2004 ; Müller et al, 2009 ). Collectively, these findings support the notion that CNP is a prominent regulatory factor in the nervous system ( Kuhn, 2016 ; Regan et al, 2021 ).…”
Section: Discussionsupporting
confidence: 83%
“…CNP is now regarded as an autocrine/paracrine regulator with broad expression in the body [ 23 ]. CNP produces a series of biological effects by the cGMP signaling pathway through binding to its specific natriuretic peptide receptor B (NPR-B) [ 24 , 25 ], such as regulation of the proliferation of myocardial cells [ 26 ]; maintaining cardiovascular homeostasis [ 27 ]; inhibition of bone growth and cartilage development [ 28 ]; promote follicular development [ 29 ]. Our group’s previous studies have already shown that CNP can induce sperm capacitation in normal people through cGMP [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that AMPK is crucial for the adaptive properties of astrocytes upon cellular insult; hence, we sought to further characterize the involvement of AMPK in the control of astrocytic functions, and in particular, the regulation of glutamate uptake. We therefore used the C6 astrocytoma cell line [ 35 ], as a reliable astrocyte-like cell model that has been used for decades to study astrocyte biology [ 36 , 37 , 38 ]. We genetically modified this cell line to allow manipulation of AMPK activity through the overexpression of a dominant negative AMPKα 1 isoform.…”
Section: Introductionmentioning
confidence: 99%